근육 강성도 힘 피드백을 이용한 하지 보조기의 무릎 신전 운동 보조 특성 분석 - 김경; 강승록; 정구영; 주수종; 김남균; 권대규; Kim, K; Kang, S.R; Jeong, G.Y; Joo, S.J; Kim, N.G; Kwon, T.K (Journal of biomedical engineering research, 2010)
The lower limb orthosis with a pneumatic rubber actuator, which is intended for the assistance and the enhancement of muscular activities of lower limbs was developed in this study. Compared to other knee extension assistive devices being developed by other researchers, our device is designed especially for the elderly people and intended only for slight assistance so that the subjects can keep their muscular strength. For the effectiveness of system, muscular activities of major muscles in lower limbs during sit-to-stand (STS) and squat motion were measured and analyzed. Subjects were performed the STS and squat motion with and without lower limb orthosis. We made comparison muscular activities between with and without lower limb orthosis. Lower limb orthosis was controlled using muscular stiffness force feedback that is controlled by muscular activities of the measured muscle from force sensor. For analysis of muscular activities, electromyography of the subjects was measured during STS and squat motion, and these were measured using MP 150(BIOPAC Systems, Inc.). Muscles of interest were rectus femoris(RF), vastus lateralis(VL), vastus medialis(VM) and vastus intermedius(VI) muscles in lower limbs of the right side. A biodex dynamometer was used to measure the maximal concentric isokinetic strength of the knee extensors of wearing and not wearing orthosis on right side. The test were performed using the concentric isokinetic mode of test with the velocity set at 60°/s for muscles around the knee joints. The experimental result showed that muscular activities in lower limbs wearing orthosis using muscular stiffness force of a vastus medialis muscle was reduced and knee extension torque of an knee joint wearing lower limb orthosis was increased. With this, we confirmed the effectiveness of the developed lower limb orthosis.